Background review for the 2016 European guideline on Mycoplasma genitalium infections. (7th September 2016) - Jensen, J.S.; Cusini, M.; Gomberg, M.; Moi, H.
Abstract: Mycoplasma genitalium is a cause of 10–35% of non‐chlamydial non‐gonococcal urethritis in men and in women, and is associated with cervicitis and pelvic inflammatory disease (PID). Transmission of M. genitalium occurs through direct mucosal contact. In women, symptoms include vaginal discharge, dysuria or symptoms of PID – abdominal pain and dyspareunia. In men, urethritis, dysuria and discharge predominates. Asymptomatic infections are frequent. In this review, we present the evidence base for the recommendations in the 2016 European guideline on M. genitalium infections and describe indications for testing, recommended diagnostic methods, treatment and patient management. The guideline was prepared on behalf of the European branch of The International Union against Sexually Transmitted Infections; the European Academy of Dermatology and Venereology; the European Dermatology Forum; the European Society of Clinical Microbiology and Infectious Diseases; the Union of European Medical Specialists. The European Centre for Disease Prevention and Control and the European Office of the World Health Organisation also contributed to their development.